PENGHAPUSAN MEREK TERDAFTAR YANG TIDAK DIPERGUNAKAN DALAM 3 TAHUN (Studi Putusan Pengadilan Niaga pada Pengadilan Negeri Medan No. 03/Merek/2013/PN/Niaga/Medan) - MANOGAR SIGALINGGANG (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Saidin, SH, MHum2. Dr. Jelly Leviza, SH, MHum3. Dr. T. Keizerina Devi A, SH, CN, MHum A brand is a sign which is exposed graphically as an image, logo, name, words, letters, figures, and color structure, in the form of 2 and/or 3 dimensions, sound, holograms, or combination of 2 or more elements to differentiate goods and/or service produced by people or legal entity in commercializing goods and/or services. The research used juridical normative method by conducting library research while the nature of the research was descriptive analytic.The result of the research shows that a registered brand which has not been used for three years consecutively can be claimed to be eliminated by the third party since the date it was first registered by the Directorate of Brand. The procedure is that the third party files a claim to the commercial court and to the Supreme Court. The conclusion is that a brand which has not been used by its owner for three years consecutively is by giving balanced and fair legal protection to its holder, and third party that wants to file a claim should have good faith. The District Court which examines and adjudicates cases on dispute in eliminating registered brands with the third party that has good faith consider and implement the regulation in Article 74, paragraph 1 of Law No. 20/2016 on Brand and Geographical IndicationKeywords: Eliminating Registered Brand, Unused Brand